Disseminated adenovirus infection in kidney transplant recipient. (April 2014) - Dawood, Ubaidullah S; Nelson, Adam; Wu, Danielle; Otto, Sophia; Russ, Graeme R
Abstract: Adenoviruses are common pathogens that have the potential to cause opportunistic infections with significant morbidity and mortality in immunocompromised hosts. The significance of adenoviral infection and disease is incompletely known in the setting of kidney transplantation. Reported adenovirus infections in renal transplant recipients have typically manifested as haemorrhagic cystitis and tubulointerstitial nephritis. Pneumonia, hepatitis and enteritis are often seen in other solid organ recipients. However, disseminated or severe adenovirus infections, including fatal cases, have been described in renal transplant recipients. There is uncertainty regarding monitoring and treatment of this virus. Although not supported by randomized clinical trials, cidofovir is used for the treatment of adenovirus disease not responding to reduction of immunosuppression. We present a case series of 2 patients with disseminated adenovirus infection in our centre who presented at different times from the time of transplantation.